2015
DOI: 10.1007/s00392-015-0911-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome after percutaneous treatment of de novo coronary bifurcation lesions using first or second generation of drug-eluting stents

Abstract: In de novo coronary bifurcation lesions treated with provisional T-stenting, SES and EES/ZES achieved better outcomes than PES by reducing the need for reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Several studies have consistently demonstrated that a single-stent provisional strategy of stenting just the main branch (MB) has better clinical outcomes compared to double-stent techniques for bifurcation lesions. However, approximately 35% of patients require crossover to two stent strategy due to compromise of the side branch which often occurs due to plaque or carinal shift 9 . Side branch(SB) rewiring is difficult and time consuming in such cases and can cause prolonged impairment of flow leading to peri procedural MI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have consistently demonstrated that a single-stent provisional strategy of stenting just the main branch (MB) has better clinical outcomes compared to double-stent techniques for bifurcation lesions. However, approximately 35% of patients require crossover to two stent strategy due to compromise of the side branch which often occurs due to plaque or carinal shift 9 . Side branch(SB) rewiring is difficult and time consuming in such cases and can cause prolonged impairment of flow leading to peri procedural MI.…”
Section: Discussionmentioning
confidence: 99%
“…This permits much better stent strut apposition to the vessel wall, promoting endothelial healing, and decreasing neointima proliferation, respectively, resulting in less restenosis. Recently, Ferenc et al [24] analysed their results on 2197 patients after stenting coronary bifurcations with different generations of DES. Patients treated with paclitaxel eluting stent (PES) had significantly higher rates of MACE compared with patients treated with sirolimus-eluting stents (SES) or zotarolimus eluting stents (ZES)/everolimus eluting stents (EES): the hazard ratio (HR) (95% CI) of PES vs. SES was 1.34 (1.04-1.71), p = 0.023, and that of PES vs. EES/ZES was 1.75 (1.19-2.57), p = 0.004.…”
Section: What Do the Data Currently Demonstrate About Bifurcationmentioning
confidence: 99%
“…Historically, PCI of bifurcation lesions are known to be associated with poorer procedural success, thus with worse clinical outcomes when compared with PCI of nonbifurcation lesions. 3,4 Extensive debate on the best approach for bifurcation percutaneous treatment is still ongoing. 3,[5][6][7][8] Multiple trials have tested mostly the approach of a provisional stent techniques versus the upfront treatment with two stents.…”
Section: Introductionmentioning
confidence: 99%